2018
DOI: 10.1177/0972150917713860
|View full text |Cite
|
Sign up to set email alerts
|

Future Apparel Buying Intention: Mediating Effect of Past Apparel Buying Behaviour and Past Apparel Buying Experience

Abstract: Apparel buying behaviour is influenced by various factors like consumer attitude, store attributes, external factors, product attributes, etc. Besides, factors like the past apparel buying behaviour of the consumers and the past apparel buying experience may also have significant influence in the future apparel buying intention of apparel. This study aims at the effect of various factors on future apparel buying intention and also the mediating effect of past apparel buying behaviour and past apparel buying ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Based on mobile service provider selection model (Alamro & Rowley, 2011;Kugyte & Sliburyte, 2007) and cognitive dissonance theory (Festinger, 1957), this study investigates the determinants of customers' choice and continuance intention with mobile data service provider by incorporating the impact of past experience with voice and SMS services on customers' brand choice and continuance intentions with mobile data service provider. It is pertinent to mention that the results presented in a recent article published in Global Business Review by Krishnakumar (2018) showed that there were partial mediating effects of past apparel buying behaviour and past apparel buying experience on future apparel buying intention. Furthermore, an important finding of our study is that the factors that attract a customer to a mobile service provider are significantly different from what keeps customers with that provider.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on mobile service provider selection model (Alamro & Rowley, 2011;Kugyte & Sliburyte, 2007) and cognitive dissonance theory (Festinger, 1957), this study investigates the determinants of customers' choice and continuance intention with mobile data service provider by incorporating the impact of past experience with voice and SMS services on customers' brand choice and continuance intentions with mobile data service provider. It is pertinent to mention that the results presented in a recent article published in Global Business Review by Krishnakumar (2018) showed that there were partial mediating effects of past apparel buying behaviour and past apparel buying experience on future apparel buying intention. Furthermore, an important finding of our study is that the factors that attract a customer to a mobile service provider are significantly different from what keeps customers with that provider.…”
Section: Discussionmentioning
confidence: 99%
“…It is pertinent to mention that the results presented in a recent article published in Global Business Review by Krishnakumar (2018) showed that there were partial mediating effects of past apparel buying behaviour and past apparel buying experience on future apparel buying intention. Furthermore, an important finding of our study is that the factors that attract a customer to a mobile service provider are significantly different from what keeps customers with that provider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future experiential intentions Swan and Trawick (1981) define future intentions as a planned individual behavior which is to be acted in the future in respect to behavior observed. According to Krishnakumar (2018), the past purchasing experience that the consumer experiences in recent previous purchases may have significant influences on the future apparel purchasing behavior. The future experiential intentions in this paper are defined as the subjective experiential judgments about how a casino gambler will behave in the future and usually serve as one criterion variable in much research focusing on service sector and satisfaction models (Soderlund and Ohman, 2003).…”
Section: Experiential Relationship Qualitymentioning
confidence: 99%
“…Consumer purchase decision is a respond toward a problem they perceived. Before reaching the decision, consumers usually collect and process information, evaluate, and choose the best option to solve their problems or making purchase decision (Krishnakumar, 2018). This concept is defined by (Prasad & Jha, 2014) as an alternative option of the existing choices to finish the variating processes in the purchasing situation.…”
Section: Introductionmentioning
confidence: 99%